RETRACTED: Pengembangan tes keterampilan dasar olahraga bola tangan bagi mahasiswa - Susanto, Ermawan (Jurnal Penelitian dan Evaluasi Pendidikan, 2017)
RETRACTED Following a rigorous and careful concerns and consideration in the review of the article published in Jurnal Penelitian dan Evaluasi Pendidikan entitled "Pengembangan tes keterampilan dasar olahraga bola tangan bagi mahasiswa" Vol 21, No 1, pp. 116-125, June 2017, DOI: https://doi.org/10.21831/pep.v21i1.15784 This paper has been found to violate the principles of Jurnal Penelitian dan Evaluasi Pendidikan publication and has been retracted. The article has contained redundant material and throughout a careful examination, the editor has found that the paper has also been published in Jurnal Pendidikan Jasmani Indonesia, Vol. 12, No. 2, pp. 110-116, November 2016, DOI: https://doi.org/10.21831/jpji.v12i2.17110 The document and its content have been removed from Jurnal Penelitian dan Evaluasi Pendidikan, and reasonable effort should be made to remove all references to this article.